Functional architecture of the cortico-basal ganglia circuitry during motor task execution: Correlations of strength of functional connectivity with neuropsychological task performance among female subjects - Marchand, William R.; Lee, James N.; Suchy, Yana; Garn, Cheryl; Chelune, Gordon; Johnson, Susanna; Wood, Nicole (Human brain mapping, 2013)
The primary aim of this study was to enhance our understanding of the functional architecture of the cortico‐basal ganglia circuitry during motor task execution. Twenty right‐handed female subjects without any history of neuropsychiatric illness underwent fMRI at 3 T. The activation paradigm was a complex motor task completed with the nondominant hand. Analyses of functional connectivity strength were conducted for pairs of structures in input, intrinsic, and output segments of the circuitry. Next, connectivity strengths were correlated with results of neurocognitive testing conducted outside of the scanner, which provided information about both motor and cognitive processes. For input pathways, results indicate that SMA–striatum interactions are particularly relevant for motor behavior and disruptions may impact both motor and cognitive functions. For intrinsic pathways, results indicate that thalamus (VA nucleus) to striatum feedback pathway appears to have an important role during task execution and carries information relevant for motor planning. Together, these findings add to accumulating evidence that the GPe may play a role in higher order basal ganglia processing. A potentially controversial finding was that strong functional connectivity appears to occur across intrinsic inhibitory pathways. Finally, output (thalamus to cortex) feedback was only correlated with motor planning. This result suggests circuit processes may be more relevant for future behaviors than the execution of the current task. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.